The Structural and Thematic Evolution of Education for Sustainable Development Research in Asia: A Bibliometric and Network Analysis - Antarjyami Mahala; Bhavin Chauhan (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
Despite growing global commitment to the Sustainable Development Goals (SDGs), the development of Education for Sustainable Development (ESD) research remains uneven across regions, with limited understanding of its structural and thematic dynamics in Asia. Existing studies are largely descriptive and lack theoretical integration, particularly in explaining how knowledge production, collaboration, and thematic evolution interact within regional research systems. This study addresses this gap by examining the structural and thematic evolution of ESD research in Asia. Using a theory-informed bibliometric and network analysis, the study analyzes 1,700 Scopus-indexed journal articles published between 2019 and 2023. The analytical framework integrates performance indicators, coauthorship network analysis, and keyword co-occurrence mapping. The results reveal three key patterns: (1) a high concentration of research output in a small number of countries and institutions, indicating structural asymmetry; (2) moderately connected but highly modular collaboration networks, suggesting fragmented knowledge diffusion mediated by central actors; and (3) a thematic structure anchored in sustainability and SDGs, alongside the rapid emergence of digital learning and artificial intelligence. These findings suggest that ESD research in Asia is evolving as a semi-integrated knowledge ecosystem shaped by uneven research capacity and global policy influence. This study advances the literature by integrating structural, relational, and thematic dimensions within a theory-informed bibliometric framework. The findings provide practical implications for strengthening regional collaboration and aligning digital innovation with the transformative goals of sustainability education.